2021
DOI: 10.55018/janh.v3i2.2
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Referral Delay Factors

Abstract: Background: Maternal Mortality Rate (MMR) is one indicator to see the health status of women. Maternal mortality is a very important problem for received attention because death does not only affect women, but also affects the health conditions of families and communities. This is because women are the main pillars in the family who play an important role in educating children, providing health care in the family, and helping the family economy. Maternal mortality rate is an indicator that reflects maternal he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 1 publication
0
6
0
1
Order By: Relevance
“…Low Nutritional Status: Due to lack of influential background, women must face discrimination as their dietary requirements are ignored during pregnancy. As a matter of fact, a healthy diet is highly essential for women during conceiving and after delivery of baby as they affect her health extensively (Ashari, 2021). Lack of sufficient and appropriate nutrition can adversely influence her health leading to several maternal complications.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Low Nutritional Status: Due to lack of influential background, women must face discrimination as their dietary requirements are ignored during pregnancy. As a matter of fact, a healthy diet is highly essential for women during conceiving and after delivery of baby as they affect her health extensively (Ashari, 2021). Lack of sufficient and appropriate nutrition can adversely influence her health leading to several maternal complications.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They state that pale ghostly faces of pregnant women horrify them when they come with their maternal complications (Geller et al, 2018). The dietary requirement of women is not given preference over men and children (Ashari, 2021). The maternal health workers, being related to rural households, observed that poverty in addition to lack of power within the family structure cause delay of pregnant women in approaching healthcare.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The incidence of stroke in the world is estimated at 200 per 100,000 population in a year (American Stroke Association, 2018) while the incidence of stroke in Indonesia in 2018 is estimated to be 500,000 people with stroke prevalence increasing from 7% to 10.9% (Ain, 2021;Riskesdas, 2018). Low muscle strength which results in dependence on daily activities in post ischemic stroke patients by 85% and 55%-75% continues to be functional limitations (Ashari, 2021;Yang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Immunization is one of the preventative measures to spread the disease to other regions, which has proven to be very cost-effective (Darrah et al, 2020;Gheibi Hayat & Darroudi, 2019). Immunization activities are expanded into an immunization development program in the context of preventing the transmission of several diseases that can be prevented by immunization, namely tuberculosis, diphtheria, pertussis, measles, polio, tetanus, and hepatitis B. Immunization is an effort to prevent infectious diseases which are one of the priority activities of the Ministry of Health as a tangible form of government commitment to achieving Sustainable Development Goals (SDGs), significantly to reduce child mortality (Ashari, 2021;Shell, 2018) Based on data from the World Health Organization (WHO) in 2014, infant mortality due to infectious diseases that should have been prevented by immunization is still high. An estimated 2-3 million deaths per year globally have been successfully prevented from diphtheria, measles, pertussis, pneumonia, polio, rotavirus diarrhea, rubella, and tetanus through immunization (Bangura et al, 2020;Darrah et al, 2020).…”
Section: Introductionmentioning
confidence: 99%